If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p=-2
We simplify the equation to the form, which is simple to understand
p=-2
We move all terms containing p to the left and all other terms to the right.
+1p=-2
We simplify left and right side of the equation.
+1p=-2
We divide both sides of the equation by 1 to get p.
p=-2
| 9-4x=-3 | | 5a^2-an-22b^2=0 | | 789489489489789789789=4x^2-4x^2+4 | | 6y^2-4y+5= | | 0=a+6a^2+9a^3+16 | | x=42 | | 12h=9n+84 | | 16c^3+52c^2-48c=0 | | 16n-10=54 | | 4x^3+6x^2-40x=0 | | 765+7-4=534-5x | | 18x+78=281-11x | | 2x(60-3x)6+15=15x+50 | | 7x^2+34x-5= | | 15u^2-34u+15=0 | | 7b+17-9b+15= | | 9a^3-18a^2-7a-16=0 | | 4x+17=33 | | 4x^3+6x^2-40=0 | | 3v^2+8v-3=0 | | 5x-16=49 | | 80t+4=100 | | 15a-60a=0 | | x^2+x+202=0 | | 8a^2-48a+64=0 | | Z=3x-4y | | 6y-7=55 | | 3(4+5m)-12+(-3m)= | | 34-2a=-8(2a-6) | | 5z+3=-22 | | 5n=3n+.26 | | 3x^2+1x+1=10 |